165k views
4 votes
Level: Standard

2) Given: -2(x - 4) = 3(x + 12); Prove: x = -5.6
Statements
Reasons

Level: Standard 2) Given: -2(x - 4) = 3(x + 12); Prove: x = -5.6 Statements Reasons-example-1

2 Answers

6 votes

-2(5-4)=4(6+12)

-10+8=24+48

-2=72

=-36

User Nekomatic
by
5.8k points
5 votes

Answer:

Explanation:

-2(x - 4) = 3(x + 12) {Use distributive rule}

-2*x - 4 *(-2) = 3*x + 12*3

-2x + 8 = 3x + 36 {add 2x to both sides}

8 = 3x + 36 +2x

8 = 5x + 36

8 - 36 = 5x {subtract 36 from both sides}

-28 = 5x

5x = -28 {Divide both sides by 5}

x = -28/5

x = -5.6

User George Herolyants
by
6.3k points